Association of the extent of return to fasting state 2-hours after a glucose challenge with incident prediabetes and type 2 diabetes: The CARDIA study. (October 2021) - Vivek, Sithara; Carnethon, Mercedes R.; Prizment, Anna; Carson, April P.; Bancks, Michael P.; Jacobs, David R.; Thyagarajan, Bharat
Highlights: Normoglycemic individuals have varying risks of developing type 2 diabetes. 2hPG - FPG > 0.9 mmol/L was associated with higher diabetes incidence over 20 years. Abstract: Aim: To evaluate whether the extent of return to fasting state 2-hours after a glucose challenge among normoglycemic individuals is associated with lower risk of incident prediabetes/ type 2 diabetes in the Coronary Artery Risk Development in Young Adults (CARDIA) cohort study. Methods: We evaluated this association among 1879 normoglycemic adults who were categorized into three groups: 'Low post load' (2hPG < FPG); 'Medium post load' (2hPG ≥ FPG and < 75 th percentile of the difference); and 'High post load' (2hPG > FPG and ≥ 75 th percentile of the difference). We used Cox proportional hazards regression to evaluate the association of the difference in 2hPG and FPG with incident diabetes/prediabetes after adjustment for demographic and clinical covariates. Results: During 20 years of follow-up, 8% developed type 2 diabetes and 35% developed prediabetes. Compared to those with 'Low post load', the risk of type 2 diabetes was higher for participants with 'High post load' [HR: 1.56, 95% CI (1.03, 2.37)] and similar for participants with 'Medium post load' [HR: 0.99, 95% CI (0.64, 1.52)]. However, HRs for incident prediabetes among participants with 'High post load' [HR = 1.2, 95 %CI = (0.98, 1.46)] was not significantly different compared to participants with 'Low post load'. Conclusion: Among normoglycemic individuals, a difference between 2hPG and FPG concentration > 0.9 mmol/L can be used to stratify individuals at higher risk for developing type 2 diabetes.